Iwahig. (Ortigas Center, Pasig Center : Viva Video Inc, 2003)
Set in 1968, Manila. Alex Zaragoza finds his mother and sister dead after a robbery in their house. Rage fills his heart and prompting him to murder one of the killers. As a result, he is sentenced to spend six to twelve years in prison. Fast forward to 1975, Palawan, Alex and a couple of his inmates is sent to Iwahig, a prison and penal farm situated 30 minutes from Puerto Prinsesa. After seven years of being imprisoned he begins to be comfortable with his co-prisons. Despite that, he still seeks to avenge the death of his loved ones and vows that, after his term, he will look for the other killer...not knowing that the one he's been looking for many just be around the corner...